Transmembrane Sema4E Guides Branchiomotor Axons to Their Targets in Zebrafish - Xiao, Tong (J Neurosci, 2003)
Class 4 semaphorins are a large class of transmembrane proteins that contain a sema domain and that are expressed in the CNS, but their in vivo neural function is unknown. In zebrafish, the epithelial cells that line the pharyngeal arches express Sema4E. Extension of branchiomotor axons along the mesenchymal cells bounded by these epithelial cells suggests that Sema4E may act as a repulsive guidance molecule to restrict the branchiomotor axons to the mesenchymal cells. To test this hypothesis, Sema4E was misexpressed in hsp70 promoter-regulated transgenic zebrafish in which sema4E was heat-inducible, and Sema4E was knocked down by injection of antisense morpholino oligonucleotides that acted specifically against Sema4E. Ubiquitous induction of Sema4E retarded outgrowth by the facial and gill branchiomotor axons significantly. Furthermore, outgrowth by gill motor axons was specifically inhibited when Sema4E-expressing transgenic cells were transplanted to their pathway in nontransgenic host embryos. Morpholino knockdown of Sema4E caused facial motor axons to defasciculate and follow aberrant pathways. These results show that Sema4E is repulsive for facial and gill motor axons and functions as a barrier for these axons within the pharyngeal arches.